Preprocessing And Clustering Short Time-Series Microarray - Loh, Wei Ping (2008)
In this thesis, we addressed a general survey on issues dealing with clustering time-series microarray. Two sets of temporal microarray study data originate from Nonobese Diabetic mice (NOD mice) species; publicly available at RAO (RNA Abundance Database) and Drosophila Melanogaster species expression data; available at GEO (Gene Expression OMR Datasets) are employed.